An evaluation of the national policy of parental involvement in their children's education and schools - Bleach, Margaret Josephine (Trinity College (Dublin, Ireland). School of Education, 2008)
An Evaluation of the National Policy of Parental Involvement in their Children’s Education and Schools This research evaluates, from the perspectives of parents, how the national policy of parental involvement in their children’s education is being implemented in five Catholic primary schools in North Dublin. Two schools have disadvantage status, which entitles them to the services of a Home School Community Liaison teacher. The other two are in a middle class area and are reliant on the good will of the Board of Management, the Principal and the Parents’ Association. The fifth school, which my daughters attended, is in a middle class area.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin